Audiovisual integration supports face–name associative memory formation. Issue 4 (2nd October 2017) - Lee, Hweeling; Stirnberg, Rüdiger; Stöcker, Tony; Axmacher, Nikolai
ABSTRACT: Prior multisensory experience influences how we perceive our environment, and hence how memories are encoded for subsequent retrieval. This study investigated if audiovisual (AV) integration and associative memory formation rely on overlapping or distinct processes. Our functional magnetic resonance imaging results demonstrate that the neural mechanisms underlying AV integration and associative memory overlap substantially. In particular, activity in anterior superior temporal sulcus (STS) is increased during AV integration and also determines the success of novel AV face–name association formation. Dynamic causal modeling results further demonstrate how the anterior STS interacts with the associative memory system to facilitate successful memory formation for AV face–name associations. Specifically, the connection of fusiform gyrus to anterior STS is enhanced while the reverse connection is reduced when participants subsequently remembered both face and name. Collectively, our results demonstrate how multisensory associative memories can be formed for subsequent retrieval.